Development and Validation of an Inventory to Evaluate Teaching Strategies for Promoting Higher-Order Thinking Skills in the Teaching of Islamic Education - Nor Hasnida Che MD Ghazali; Norfishah Mat Rabi; Norwaliza Abdul Wahab; Nor Aizal Akmal Rohaizad (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2017)
The purpose of this study is to develop and assess the validity and reliability of an inventory on teaching strategies involved in promoting HOTs as well as to identify the most and the least popular teaching strategies used. The inventory is adapted from Gulistan et al. (2016). It is in the form of questionnaire distributed to a sample of 220 primary school teachers teaching Islamic education subject. The content validity is assessed by the experts and the construct validity is measured by Exploratory Factor Analysis. The reliability of the instrument is measured using internal consistence reliability, which is alpha coefficient reliability or Cronbach Alpha. Results of exploratory factor analysis suggested that 5 items need to be removed due to their non-dimensionality as they have more or less equal loadings on several factors. The instrument developed yielded high values of internal consistency as reflected by the Cronbach alpha values. Thus, the final draft of the instrument contains 26 items which are valid and reliable. Even though the validity and reliability of the instrument are within the acceptable range, more data need to be gathered using a bigger sample size, and further analysis using confirmatory factor analysis could be used to explore deeper into the psychometric characteristics of the items before the instrument can be finalized. Furthermore, the findings of the study indicated that the most popular strategy used among teachers teaching Islamic education was the strategy for acquiring knowledge which introduces students more on memorizing basic concepts, while the least used strategy was the higher cognitive skills teaching strategies such as problem solving, collaborative learning and inquiry strategies.